pre cal
posted by jason on .
solve for x:
x^(2/3)=(1/27)
(2^(x)+4)/(2^x)=2
explain please

For the first one, remember that (a^b)^c = a^(bc). 2/3 * 3/2 = 1, so raise each side to the power of 3/2. That's all you need to do; you'll be left with x=(something).
For the second, start by splitting the left side into two fractions, like so:
(2^x)/(2^x) + 4/(2^x) = 2.
(2^x)/(2^x) = 1, so we can subtract that from both sides:
4/(2^x) = 1.
Multiply by 2^x to get that to itself:
4 = 2^x.
And you should be able to finish it yourself.